MO267: Traditional and Disease-Related Cardiovascular Risk Factors in Anca-Associated Vasculitis: A Prospective, Two-Centre, Observational Cohort Study. (3rd May 2022) - Vegting, Yosta; Lars Penne, Erik; Hilhorst, Marc; Pagnoux, Christian; Houben, Eline
Abstract: BACKGROUND AND AIMS: ANCA-associated vasculitis (AAV) has been associated with increased risk of cardiovascular (CV) events. The purpose of the present study was to asses cardiovascular risk determinants and outcomes in a two-centre prospective cohort of AAV patients. METHOD: Prevalent patients diagnosed with AAV ≥ 3 months were recruited over a period of 8 months from the Northwest Clinics in the Netherlands and 3 months from the Mount Sinai Hospital in Canada, and followed for 3–5 years. A comprehensive CV risk assessment was performed at inclusion. Subjects were followed up yearly until the first cardiovascular event, death or end of follow-up, whichever came first. Cardiovascular events were assessed by an independent outcome panel. Cox proportional hazards analyses were performed to relate baseline characteristics to the first CV event. RESULTS: A total of 144 patients were included (median age 64.6 years, male sex 56%, median BVAS score 0, median Framingham risk score 14.3%). After a median follow-up of 2.91 years, 28 non-fatal and 4 fatal CV events were registered in 16 patients. Twelve patients died of non-cardiovascular causes. The incidence of fatal and non-fatal CV events was 5.5 per 100 patient-years. In a univariable analysis an association was found between traditional risk factors and risk of CV events [hazard ratio (HR) (95% confidence interval)], including age [HR 1.08 (95% CI 1.03–1.14)], HbA1c [HR 1.59 (95% CI 1.15–2.22)], systolic blood pressure [HR 1.04, 1.01–1.06), history of CV event [HR 3.47 (95% CI 1.29–9.32)] and Framingham risk score [HR 1.05 (95% CI 1.03–1.08)]. After adjusting for age and sex, HbA1c [HR 1.70 (95% CI 1.17–2.48)] and previous CV event [HR 2.90 (95% CI 1.02–8.21)] remained significantly associated with CV events. In a multivariable cox regression analysis (adjusted for Framingham risk score), a longer disease duration was associated with CV events [HR 1.08 (95% CI 1.01–1.16)]. CONCLUSION: The present study is the largest prospective study on CV risk in patients with AAV and showed that CV risk was driven by both traditional and disease-related risk factors. Disease duration is associated with increased risk of CVE, but which precise disease-related factors accounts for this finding, and whether it can be acted upon remain to be determined.